FDI and Indirect Taxes - Sector Approach: The Case of Turkey - Akbulut, Hale; Yereli, Ahmet Burcin (International Journal of Economics and Financial Issues, 2017)
This study aims to investigate the relationship between indirect taxation and foreign direct investments in Turkey. We benefit from a quarterly data set covering the period 2006:Q1-2016:Q1 and employ bounds testing approach of Pesaran et al. (2001). We also employ error correction model in order to determine short-run coefficients. Our results obtained from bounds test confirm the cointegration relationship between total indirect taxes and foreign direct investments. We also expand our analysis by focusing on the effects on sub-sectors. While the bounds testing approach confirms the cointegration relationship between indirect taxes and foreign direct investments in manufacturing sector, we find no evidence for a cointegration relationship in the tertiary sector. The test result is also inconclusive for agricultural sector. Moreover, the results of error correction models suggest no statistically significant effects in the short-run. Keywords: fiscal policy, indirect taxes, tax competition. JEL Classifications: E60, E62.